Evaluation of the Efficiency of Ammonia Removal from Aqueous Medium Using Inexpensive Adsorbent Obtained from Walnut Shell - Mahmud Mohammadyan; Mahdi Ghorbanian; Elham Rahmanzadeh; Jamshid Yazdani Charati; Esmael Babanejad; Sepideh kamali (Mazandaran University of Medical Sciences, 2021)
Introduction and Objectives: Ammonia is a colorless gas with a pungent and corrosive odor that can cause serious damages to human health and the environment. Ammonia is used in the industries of pharmacology, tanning, and silvering mirrors and the production of military explosives. This study aimed to investigate the efficiency of inexpensive adsorbent obtained from the walnut shell in the surface absorption of ammonia from water and the parameters affecting it. Materials and Methods: In this quasi-experimental interventional study, charcoal of walnut shell was used and the effects of carbonization temperature, pH, ammonia concentration, adsorbent dose, and contact time on the adsorption of ammonia from the aqueous medium were investigated. Ammonia concentration was measured by a spectrophotometer at 640 nm. More than 712 samples were analyzed for this study. Results: In this study, the highest efficiency of ammonia removal from an aqueous medium was obtained at optimal pH 8, carbonization temperature of 850°C, and adsorbent dose of 20 g/l. According to the obtained adsorption capacity, the optimal concentration for ammonia removal was considered 60 mg/l. The results showed that the experiments followed the Freundlich isotherm (R²=0.9949). Kinetic studies also indicated a higher correlation with the first-order equation. Conclusions: Based on the results of this study, it can be stated that the adsorbent obtained from the walnut shell, as a natural adsorbent, is able to remove a relatively desirable amount of ammonia from aqueous medium and is recommended for other environmental pollutants due to its high adsorption capacity.